Endophytic Bacteria in Highland and Its Ability To Enhance Plant Growth Environment - Siti Maryam Yasin; Elkawakib Syam’un; Burhanuddin Rasyid (Journal of Global Innovations in Agricultural Sciences)
The objective of this study was to isolate and characterize endophytic bacteria from the rhizosphere of local highland North Luwu rice, which exhibits the ability to promote plant development and function as a biofertilizer. The research was conducted in the Pest Science Laboratory, Department of Pests and Diseases, Hasanuddin University, South Sulawesi. The present study involved conducting morphological and physiological characterization tests, índole-3-acetic acid producing bacteria ability test, and phosphate dissolution test seed growth test in vitro and identified using the 16S rRNA sequencing method. This study successfully isolated 22 bacterial isolates from soil samples and rhizospheres of local rice varieties. Morphological characterization showed different results in color, size, and shape. Testing the ability of índole-3-acetic acid bacteria from isolates of local rice rhizosphere bacteria of the Bandarata rice variety produced the brightest pink hue (3.39 milligrams per liter). The local tarone hoyane rice variety can dissolve phosphate with a dissolution index value of 2.64. The results of the 16S rRNA gene sequence using the BLAST-N program showed that bacterial isolates from local North Luwu rice produced Pseudomonas bacteria. sp strain, Pseudomonas fluoresces bacteria, Pseudomonas montel strain, and Stenotrophonas sp strain. This research produced isolates of endophytic bacteria from local highland rice which can increase plant growth. Keywords: Endophytic bacteria; rice; rhizobacteria; phosphate solubilization, IAA.